Evaluation of Potential Herb-Drug Interactions Between Shengmai Injection and Losartan Potassium in Rat and In Vitro - Niu, Zhenchao; Qiang, Tingting; Lin, Wenyong; Li, Yiping; Wang, Keyan; Wang, Dan; Wang, Xiaolong (Frontiers in Pharmacology, 2022)
Aim: The present study aimed to explore the potential herb-drug interactions (HDI) between Shengmai injection (SMI) and losartan potassium (LOS) based on the expression profiles of cytochromes P450 (CYP450) and drug transporters in rat and in vitro. Methods: Different concentrations of SMI were used to explore the influence of SMI on the antihypertensive efficacy of LOS in the hypertension rat model established by N (omega)-nitro-L-arginine methyl ester (L-NAME) for 4 weeks. Subsequently, the serum concentration levels of LOS and losartan carboxylic acid (EXP3174) were determined by Liquid Chromatography Mass Spectrometry (LC-MS) and pharmacokinetic analysis. Human liver microsomes, human multidrug resistance protein 1 (MDR1/P-gp), and breast cancer resistance protein (BCRP) vesicles, human embryonic kidney 293 cell line with stable expression of the organic anion transporting polypeptide 1B1 (HEK293-OATP1B1 cells) and mock-transfected HEK293 (HEK293-MOCK) cells were used to verify the effects of SMI on CYP450 enzymes and drug transporters in vitro. Results: Low, medium, and high concentrations of SMI increased the antihypertensive efficacy of LOS to varying degrees. The high dose SMI increased the half-life (t1/2), the maximum plasma concentration (Cmax), the area under the plasma concentration-time curve (AUC) from time zero to the time of the last measurable plasma concentration (AUC0-t), AUC from time zero to infinity (AUC0-∞), and mean residence time (MRT) values of LOS and decreased its apparent volume of distribution (Vd) and clearance (CL) values. The AUC0-t, AUC0-∞, and MRT of LOS were increased, whereas the CL was decreased by the medium concentration of SMI. In addition, the high, medium, and low doses of SMI increased the relative bioavailability (Frel) of LOS. SMI exhibited no significant effects on the pharmacokinetics of EXP3174. In vitro, SMI exhibited different suppressive effects on the enzyme activity levels of CYP1A2 (6.12%), CYP2B6 (2.72%), CYP2C9 (14.31%), CYP2C19 (12.96%), CYP2D6 (12.26%), CYP3A4 (3.72%), CYP2C8 (10.00–30.00%), MDR1 (0.75%), OATP1B1(2.03%), and BCRP (0.15%). Conclusion: In conclusion, SMI improved the antihypertensive efficacy of LOS in the L-NAME-induced hypertension rat model by increasing the concentration of LOS, while leaving the concentration of EXP3174 intact. SMI affected the pharmacokinetic properties of LOS by decreasing the elimination of LOS. These effects might partly be attributed to the inhibition of the activities of CYP3A4, CYP2C9, and of the drug transporters (P-gp, BCRP, and OATP1B1) by SMI, which need further scrutiny.